Pathfinders in Science. Scientific expeditions at the vanguard of discovery - Josep Maria Camarasa (Mètode Science Studies Journal: Annual Review)
Any journey, even the most trivial beach-resort package tour, has an element of discovery, however dozy the traveller may be. For some, discovery may just mean getting to know new places and sharing new experiences, but there have been (and still are) certain travellers for whom discovery and the subsequent communication of their experiences represent the sole mission of their expeditions.